Efficacy of a topical concentrated surfactant gel on microbial communities in non‐healing diabetic foot ulcers with chronic biofilm infections: A proof‐of‐concept study. Issue 4 (21st January 2021) - Malone, Matthew; Radzieta, Michael; Schwarzer, Saskia; Jensen, Slade O.; Lavery, Lawrence A.
Abstract: This proof‐of‐concept study sought to determine the effects of standard of care (SOC) and a topically applied concentrated surfactant gel (SG) on the total microbial load, community composition, and community diversity in non‐healing diabetic foot ulcers (DFUs) with chronic biofilm infections. SOC was provided in addition to a topical concentrated SG, applied every 2 days for 6 weeks. Wound swabs were obtained from the base of ulcers at baseline (week 0), week 1, mid‐point (week 3), and end of treatment (week 6). DNA sequencing and real‐time quantitative polymerase chain reaction (qPCR) were employed to determine the total microbial load, community composition, and diversity of patient samples. Tissue specimens were obtained at baseline and scanning electron microscopy and peptide nucleic acid fluorescent in situ hybridisation with confocal laser scanning microscopy were used to confirm the presence of biofilm in all 10 DFUs with suspected chronic biofilm infections. The application of SG resulted in 7 of 10 samples achieving a reduction in mean log10 total microbial load from baseline to end of treatment (0.8 Log10 16S copies, ±0.6), and 3 of 10 samples demonstrated an increase in mean Log10 total microbial load (0.6 log10 16S copies, ±0.8) from baseline to end of treatment. Composition changes in microbial communities were driven by changes to the most dominant bacteria. Corynebacterium sp. and Streptococcus sp. frequently reduced in relative abundance in patient samples from week 0 to week 6 but did not disappear. In contrast, Staphylococcus sp., Finegoldia sp., and Fusobacterium sp., relative abundances frequently increased in patient samples from week 0 to week 6. The application of a concentrated SG resulted in varying shifts to diversity (increase or decrease) between week 0 and week 6 samples at the individual patient level. Any shifts in community diversity were independent to changes in the total microbial loads. SOC and a topical concentrated SG directly affect the microbial loads and community composition of DFUs with chronic biofilm infections.